Oromandibular dystonia in Yemeni patients with khat chewing: a response to botulinum toxin treatment - Hatem S. Shehata; Mohamed S. El-Tamawy; Nevin Mohieldin; Mohammed Edrees; Saeed Bohlega (MDPI AG, 2014)
Khat-(Catha edulis) related oromandibular dystonia is a difficult-to-treat subset of movement disorders that involve masticatory muscles with diverse and incapacitating manifestations. The aim of this study was to evaluate the efficacy of Botulinum toxin-type A therapy in khat chewer Yemeni patients with oromandibular dystonia. This prospective study included 18 khat-chewers Yemeni patients with refractory oromandibular dystonia, who were subjected to Botulinum toxin-A injection and followed up for 3 months thereafter. Primary efficacy outcome was the global impression scale, and secondary outcome measure was the Unified Dystonia Rating Scale. Patients showed improvement of both efficacy measures, maximum satisfactory responses were detected at the forth week after injection. No major adverse events were detected. Botulinum toxin-A is considered an effective and safe treatment option for refractory oromandibular dystonia in khat-chewers.